Pengembangan Ekonomi Sirkular untuk Pengelolaan Sampah Organik di Desa Senden, Kabupaten Magelang - Antriyandarti, Ernoiz; Barokah, Umi; Rahayu, Wiwit; Wuri Ani, Susi; Marwanti, Sri; Darsono; Ferichani, Minar; Irawan, Suko (Warta LPM, 2025)
Most of the waste produced by rural households is organic waste, which must be disposed of immediately because it rots quickly, emits an unpleasant odor, and can be a source of disease. Implementing a community-based circular economy at the village level can solve the accumulation of organic waste in rural areas. This circular economy model encourages downstream waste processing, thereby generating economic value. A circular economy that delivers significant financial benefits will make waste processing sustainable. Senden Village, located in Mungkid District, Magelang Regency, is one such village that has a local waste collection site (TPS). Its primary issue is the lack of techniques for processing waste, particularly organic waste, into quality products that are useful and have market value. Therefore, this Research Group Service initiative aims to develop the application of a circular economy for managing organic waste by producing organic fertilizers enriched with biological agents. The organic fertilizers produced will be highly quality and competitive in the market, thereby providing an alternative productive economic activity for the people of Senden Village. Organic waste processing into commercial products can be sustainable if it offers financial incentives for the community. This initiative aligns with the Sustainable Development Goals (SDGs), specifically goals 2, 3, and 12.